Psalm 53 in canonical perspective - Botha, Phil J. (Old Testament Essays, 2013)
Psalm 53 is an adapted version of Ps 14, crafted to fit in among a cluster of psalms consisting of Pss 52-55. Each of these psalms is described in their respective headings as a "Maskil," while Pss 52 and 54 each also have a biographical link to the time of persecution of David by Saul. It is argued that various contexts have to be taken into consideration for a full understanding of Ps 53: the differences between Pss 14 and 53; Ps 53's links to the cluster of Pss 52-55; the connections it has with Proverbs, and the connections it has with the history of David in 1 Samuel via the two biographical notes in the cluster which seem to apply to it as well. When all these contexts are taken into consideration, Ps 53 appears to be an explication of certain texts in Proverbs, as if applying the truths of wisdom teaching to the experiences of David.
free